THE NATIONALITY MOVEMENT IN GORONTALO - Hamzah Harun Al-Rasyid; Saprillah Saprillah (Balai Penelitian dan Pengembangan Agama Semarang, 2018)
Religion and nationalism are two terms that are closely related with one another. In Indonesia, the debate about religion and nationalism has narrowed down to two major issues: The first is the integration of religion and nationalism in the form of a religious state. The second is religious accommodation within the country. The Indonesian founding fathers have agreed to choose the accommodation model by making Pancasila as the foundation of the country, whose core is based on the universal values of religion, such as divinity, humanity, unity, deliberation and social justice. This research was conducted in Gorontalo city and applies qualitative method. Data collection was carried out using interview techniques and document studies. Interviews were conducted with informants ranging from religious leaders, historians, and academics. This paper aims to illustrate that the choice to accommodate religion in the country is the right action, given the national movement in Indonesia is based on religious movements. The independence movement in 1942 in Gorontalo was the culmination of the movement of nationalist movement such as Sinar Budi and Islamic-based organizations such as Syarikat Islam (SI), Muhammadiyah, Nahdlatus Sjafiiah, which had been carried out 10-20 years earlier.